Analysing Perceptions of Sharia Law Students on the Khilafah in Indonesian State Islamic Universities - Subando, Joko; Wibowo, Muhammad Kurniawan Budi; Baehaqi, Baehaqi; Firdos, Firdos; Abdulah, Nur Aina; Nurhaida, Heni Satar (Balai Penelitian dan Pengembangan Agama Semarang, 2024)
This study aims to analyze the perceptions of Sharia students toward the concept of Khilafah at State Islamic Universities in Indonesia. Using a survey method, data were collected through a validated and reliable instrument consisting of 29 questions. A total of 332 respondents from nine institutions participated in this research. Data were analyzed using descriptive statistics to evaluate various aspects of Khilafah as proposed by Taqiyuddin An Nabhani. The results indicate that Sharia students generally have a positive perception of the Khilafah concept according to Taqiyuddin An-Nabhani, with aspects such as the functions and establishment of the Khilafah receiving high ratings. However, aspects related to the form of the Islamic state and government were rated less favorably. Another finding reveals that Sharia students from outside Java have a better perception compared to students from Java, with the former being more open to accepting the views on Khilafah. This study recommends further research to This study recommends further research to understand the factors influencing these perceptions and their implications for Sharia education and broader discussions on Islamic governance.